Analysis of Crosstalk Noise for 2π RC Model considering Interconnect Parameters in Deep Submicron VLSI Circuit - Toma, Rafia Nishat; Maniruzzaman, Md.; Panjiyar, Om Prakash; Hassan, Md. Mahmud; Hasan, Md. Nazmul; Rahman, Md. Atiqur (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2019)
As the technology enters into deep sub-micron region, signal integrity is becoming a very crucial parameter. In order to deal with the challenges associated with signal integrity problem, such as, crosstalk noise and delay, estimation and minimizing techniques should be addressed with great importance. Along with this, the peak noise amplitude and noise width values in the sensitive node must be verified and confirmed that they are below the certain threshold levels. Hence, for a particular range of frequency, an accurate and efficient crosstalk noise estimation model is necessary to confirm the signal integrity. Therefore, this work aims to analyse the crosstalk noise between two interconnect lines using 2π RC model, and considering its physical parameters, such as the parasitic capacitance, resistance and inductance and interconnect parameters, specifically the spacing between two interconnects, length, width, thickness, height from substrate in deep sub-micron VLSI circuit. In this paper, analytical expressions for peak noise amplitude and noise width in 2π model with RC interconnects for unit step input were derived, and then it was simulated in MATLAB and HSPICE software platform. The MATLAB based results represent that 2π model possesses less errors, and showed better performance compared to some other popular models by adjusting the interconnecting parameters for any certain range of operating frequency. The HSPICE simulation justifies the accuracy of the approach with full satisfaction.